A Two-Mode Digital Pressure Meter Equipped With An Automatic Leak Test Using MPX5050gp And MPXv4115vc6u Sensors - Fita Florensa Rooswita; Triana Rahmawati; Syaifudin Syaifudin (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2020)
The calibration process aims to guarantee that a measurement device is to follow the established standards. The purpose of this study is to design an automatic leak test for digital pressure meter in which the function of this device is to measure pressure on the sphygmomanometer and suction pump or other devices that use pressure parameters for measurement. This study used the Arduino as a control system, and to process the analog data into digital. Signal conditioning, based on the amplifier circuit, was also applied for the MPX5050GP and MPXV4115VC6U sensor. The proposed design used a 4x20 liquid crystal display to show the parameters in this design ware also equipped with a selector of mmHg or kPa units. The result shows that the fluctuating resolution is 0.25 mmHg. In this design, an automatic leak feature was also equipped for the sphygmomanometer. The results obtained an average error of 7.3 mmHg for sphygmomanometers. On the other hand, the suction pumps have an accuracy of less than 1.5 kPa. From these results, it was concluded that this design could be used for the measurement of devices that use positive pressure and negative pressure